Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1063/1.2135383
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency surface acoustic wave devices based on LiNbO3∕diamond multilayered structure

Abstract: This research is focused on the development of a new technology for the fabrication of high-frequency surface acoustic wave (SAW) filters based on diamond and lithium niobate (LiNbO3) materials. LiNbO3 films are in situ deposited at 490 °C on polycrystalline diamond substrates by radio-frequency magnetron sputtering; a multistep growth process is proposed to deposit oriented LiNbO3 films with a smooth surface. Conventional interdigital transducers are fabricated on top of the piezoelectric LiNbO3 layer by stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Lithium niobate (LiNbO 3 ) and lithium tantalite (LiTaO 3 ) single crystals have stable ferroelectric single domain structure (3 m point group symmetry) after being poled and possess excellent temperature stability because of their high Curie temperatures (1210 °C for LiNbO 3 and 630 °C for LiTaO 3 ) [38,39]. Therefore, they have been widely used for surface acoustic wave (SAW) devices [40,41]. However, their piezoelectric constants and electromechanical coupling factors are much lower than those of BaTiO 3 materials [42,43].…”
Section: Introductionmentioning
confidence: 99%
“…Lithium niobate (LiNbO 3 ) and lithium tantalite (LiTaO 3 ) single crystals have stable ferroelectric single domain structure (3 m point group symmetry) after being poled and possess excellent temperature stability because of their high Curie temperatures (1210 °C for LiNbO 3 and 630 °C for LiTaO 3 ) [38,39]. Therefore, they have been widely used for surface acoustic wave (SAW) devices [40,41]. However, their piezoelectric constants and electromechanical coupling factors are much lower than those of BaTiO 3 materials [42,43].…”
Section: Introductionmentioning
confidence: 99%
“…Among those materials having interesting electro-optic and piezoelectric coefficients, lithium niobate (LiNbO 3 ) is a good candidate for coupling with NCD substrates. Recent studies have demonstrated its ability to be integrated in various opto-electronic and acoustooptic devices, such as filters [7], electro-optic modulators [8] or optical waveguides [9]. One of the main challenges is the growth of a uniform, smooth and well-oriented LiNbO 3 layer, to allow the diamond-based SAW to propagate.…”
Section: Introductionmentioning
confidence: 99%
“…The fundamental resonance frequency (f r ) is determined by f r = v SAW /λ, where v SAW is the speed of acoustic wave propagation at the surface, and this surface acoustic wave mode is called Rayleigh mode. LiNbO 3 [9][10][11] , LiTaO 3 12 , ZnO [3][4][5][13][14][15] , AlN [16][17][18][19] , and AlScN 20,21 are the piezoelectric materials commonly used or actively studied.…”
mentioning
confidence: 99%